Benzothioxanthene Dicarboximide as a Tuneable Electrogenerated Chemiluminescence Dye. Issue 24 (3rd December 2022) - Dauphin, Alice L.; Andrés Castán, José María; Yu, Jing; Blanchard, Philippe; Sojic, Neso; Ahn, Hyun S.; Walker, Bright; Cabanetos, Clément; Bouffier, Laurent
Abstract: Invited for this issue's Front Cover are Dr. Laurent Bouffier and Prof. Neso Sojic of the Institute of Molecular Sciences (ISM, Bordeaux) in collaboration with Dr. Clément Cabanetos (MOLTECH‐Anjou & 2BFUEL, Seoul). The cover picture shows the colour‐tuneable electrogenerated chemiluminescence collected from benzothioxanthene dicarboximide dyes. Read the full text of the Research Article at 10.1002/celc.202200967 . Abstract :